2019
DOI: 10.1038/s41598-019-53156-8
|View full text |Cite
|
Sign up to set email alerts
|

Altered lignocellulose chemical structure and molecular assembly in CINNAMYL ALCOHOL DEHYDROGENASE-deficient rice

Abstract: Lignin is a complex phenylpropanoid polymer deposited in plant cell walls. Lignin has long been recognized as an important limiting factor for the polysaccharide-oriented biomass utilizations. To mitigate lignin-associated biomass recalcitrance, numerous mutants and transgenic plants that produce lignocellulose with reduced lignin contents and/or lignins with altered chemical structures have been produced and characterised. However, it is not fully understood how altered lignin chemistry affects the supramolec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 89 publications
1
15
0
1
Order By: Relevance
“…In WEL pure a small peak was also observed at δ C 192 ppm, that was annotated as an aldehyde based on the presence of a correlation at δ C /δ H 192/9.8 in the corresponding HSQC spectrum (data not shown). 53 Nevertheless, as this HSQC correlation was also observed in WECEL pure control samples, and laccase/HBT treatment did not result in more than 1 aldehyde group per 100 aromatic rings, we concluded that aldehyde formation was not a main degradation pathway during LMS treatment. Remarkably, very clear correlations were observed that corresponded to S-ketones and S-acids (δ H 7.1-7.3), whereas the intensity of their G-analogues was very low.…”
Section: Detailed Insights Into Laccase/hbt Induced Reactions Of Ligninsupporting
confidence: 56%
“…In WEL pure a small peak was also observed at δ C 192 ppm, that was annotated as an aldehyde based on the presence of a correlation at δ C /δ H 192/9.8 in the corresponding HSQC spectrum (data not shown). 53 Nevertheless, as this HSQC correlation was also observed in WECEL pure control samples, and laccase/HBT treatment did not result in more than 1 aldehyde group per 100 aromatic rings, we concluded that aldehyde formation was not a main degradation pathway during LMS treatment. Remarkably, very clear correlations were observed that corresponded to S-ketones and S-acids (δ H 7.1-7.3), whereas the intensity of their G-analogues was very low.…”
Section: Detailed Insights Into Laccase/hbt Induced Reactions Of Ligninsupporting
confidence: 56%
“…The use of Arabidopsis represents an ideal model to quickly investigate multiple genetic engineering strategies and validate analytical method-ologies, both transposable to agronomically relevant lignocellulosic feedstock species. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] In contrast to total G CHOH and S CHOH residue levels which could only be reduced or annulled compared to WT plants, total G CHO residue content varied by roughly threefold changes in either direction in Arabidopsis with specific genetic changes, namely increasing in the cad4xcad5 mutant and decreasing in the 4cl1x4cl2 mutant ( Figure 2A). Arabidopsis natural ecotype variant Wassilewskija (WS) presented~60 % more G CHO residues than the Columbia-0 (Col-0) ecotype, although their G CHOH and S CHOH residue amounts did not differ ( Figure S2).…”
mentioning
confidence: 99%
“…[6,8] Similar increases of aldehyde residues in lignin by reducing CAD expression, using mutagenesis and transgenic approaches in poplar, tobacco, flax, brachypodium, switchgrass, rice and sorghum, have all showed either increased pulping, saccharification and/or biogas yields without affecting plant productivity. [5,[10][11][12][13][14][15][16][17][18] In fact, natural mutants in CADs thrive in the wild and have been readily identified, such as the CAD-null mutant of pine. [19,20] Natural mutants in CAD have also been selected and preferentially used in agriculture more than 100-years ago, like the Sekizaisou variety of mulberry trees, which improved both silkworm growth and silk quality when used for feed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Biomass is a complex material that is mainly composed of crosslinked hemicellulose, cellulose, and lignin, along with extracts (tannins, fatty acids, and resins) and inorganic salts 2 . Numerous studies have indicated that cellulose is the most abundant organic linear polymer 3 . It is composed of D-glucose as a basic unit and is linked via β-O-4 glycosidic bonds.…”
mentioning
confidence: 99%